2013
DOI: 10.1007/s00128-013-1000-0
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation Effect of Metolachlor on Toxicity of Organochlorine and Organophosphate Insecticides in Earthworm Eisenia andrei

Abstract: Acetylcholinesterase, glutathione-S-transferase and catalase activities were determined in earthworms Eisenia andrei exposed to insecticides (endosulfan, temephos, malathion, pirimiphos-methyl) alone and in a binary combination with the herbicide metolachlor. Metolachlor individually was not acutely toxic, even at high concentrations applied; however, in the treated earthworms metolachlor enhanced the toxicity of endosulfan and temephos by significantly reducing the acetylcholinesterase activity. In binary com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In contrast to the MTT assay, however, we did not find a potentiation effect of SM by the addition of PG in the clonogenic assay ( Figure 2B ). Stepić et al (2013) insisted that the potentiation character of chemical was a specific phenomenon, rather than a general effect, and that the reason was related to the chemical structures of the mixture. Although we found the potentiation of SM in the cell viability assay, only A549 cells were used, and only PG was mixed with SM in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the MTT assay, however, we did not find a potentiation effect of SM by the addition of PG in the clonogenic assay ( Figure 2B ). Stepić et al (2013) insisted that the potentiation character of chemical was a specific phenomenon, rather than a general effect, and that the reason was related to the chemical structures of the mixture. Although we found the potentiation of SM in the cell viability assay, only A549 cells were used, and only PG was mixed with SM in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although classified as a potential carcinogen by the U.S. Environmental Protection Agency [53], metolachlor is widespread in the United States. The actual toxicity of metolachlor on humans and ecosystems is still being analyzed [53][54][55][56], and actual effects are difficult to assess because acute toxicity mostly occurs in combination with other substances [57].…”
Section: Discussionmentioning
confidence: 99%
“…Stepic et al . [ 13 ] found that binary combinations of two pesticides atrazine and cyanazine with the organophosphate chlorpyrifos had synergism effect on non target organism. These findings call for more research to be promptly undertaken in order to understand the mechanisms behind the synergy observed and quantify the extent of its environmental impacts.…”
Section: Discussionmentioning
confidence: 99%